Science and technology in Japan - Sigurdson, Jon (Longman, 1991)
This edition provides comprehemsive coverage of the science and technology system in Japan. The book combines information on official and corporate bodies with analysis and interpretation, and covers both structures and institutions of research. Special emphasis is laid on industrial research, particularly in the private sector.